Microfluidics for pharmaceutical applications : from nano/micro systems fabrication to controlled drug delivery - Santos, Hélder A.; Liu, Dongfei; Zhang, Hongbo (Micro & nano technologies., 2019)
"Microfluidics for Pharmaceutical Applications: From Nano/Micro Systems Fabrication to Controlled Drug Delivery is a concept-orientated reference that features case studies on utilizing microfluidics for drug delivery applications. It is a valuable learning reference on microfluidics for drug delivery applications and assists practitioners developing novel drug delivery platforms using microfluidics. It explores advances in microfluidics for drug delivery applications from different perspectives, covering device fabrication, fluid dynamics, cutting-edge microfluidic technology in the global drug delivery industry, lab-on-chip nano/micro fabrication and drug encapsulation, cell encapsulation and delivery, and cell- drug interaction screening"--Publisher